Occupational and recreational physical activity and Parkinson’s disease in Denmark - Shih, I-Fan; Starhof, Charlotte; Lassen, Christina Funch; Hansen, Johnni; Liew, Zeyan; Ritz, Beate (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'This study aimed to examine whether occupational and physical activity (PA) at different ages contribute to Parkinson’s disease (PD) risk in a large population-based case-control study in Denmark. ' ' METHODS ': 'We identified 1828 PD patients from the Danish National Hospital Register and recruited 1909 gender and year of birth matched controls from the Danish Central Population Register. Occupational and leisure-time PA were determined from a job exposure matrix based on occupational history and self-reported leisure-time information. ' ' RESULTS ': 'No association was found for occupational PA alone in men, but higher leisure-time PA (≥5 hours/week of strenuous activities) in young adulthood (15–25 years) was associated with a lower PD risk (adjusted odds ratio (ORadj) 0.75, 95% confidence interval (95% CI) 0.62–0.90); men who engaged in high occupational and high leisure-time PA in young adulthood had the lowest PD risk (ORadj 0.58, 95% CI 0.41–0.81). Among women, inverse associations were found for occupation PA before age 50 (highest vs lowest, ORadj 0.75, 95% CI 0.55–1.06) and strenuous leisure-time PA after age 50 (ORadj 0.65, 95% CI 0.87–0.99); no clear pattern was seen for leisure and occupational PA combined. ' ' CONCLUSIONS ': 'We observed gender-specific inverse associations between occupational and leisure-time PA and PD risk; however, we cannot preclude reverse causation especially in older ages since PD has a long prodromal stage that might lead to a reduction of PA years before motor symptom onset and PD diagnosis.
Keywords: Denmark; exercise; job exposure matrix; leisure-time physical activity; occupational physical activity; Parkinson’s disease; physical activity; recreational physical activity; work